Out Come of Threatened Abortion in a Series of 100 Cases in RMCH (TAJ: Journal of Teachers Association, 2009)
Threatened abortion is a clinical entity where the process of abortion has started but has not progressed to a state from which recovery is impossible1. The prognosis of threatened abortion is very unpredictable whatever method of treatment is employed either in hospital or at home. 100 cases of threatened abortion were studied in RMCH. Over one year of study it was found that abortion cases constituted about 34% of all gyneacological admission. Among them 12% of all abortion related admitted cases had threatened abortion. From the results it was evident that most of the cases were between 20-30 yrs. Age group (58%), 71% were multigravida, 80% were illiterate & low socio economic condition uneventfully & discharged by giving conservative management. In the rest abortion pregnancy was terminated either by inevitable abortion or missed abortion. Follow up data showed that among 46 cases of threatened abortion who readmitted in hospital, 26 cases had normal pregnancy out come, 2 cases developed IUD, 4 cases developed preterm labour, 12 cases had placenta praevia, 2 cases had IUGR & 2 cases had aboruptio placenta. So the conclusion of the study was first trimester vaginal bleeding is an independent risk factor for adverse obstetric out come that is directly proportional to the amount of bleeding.   doi: 10.3329/taj.v18i2.3170 TAJ 2005; 18(2): 76-79